Origin of the Animal Circadian Clock: Diurnal and Light-Entrained Gene Expression in the Sponge Amphimedon queenslandica - Jindrich, Katia; Roper, Kathrein E.; Lemon, Sussan; Degnan, Bernard M.; Reitzel, Adam M.; Degnan, Sandie M. (Frontiers in Marine Science, 2017)
The circadian clock is a molecular network that coordinates organismal behavior and physiology with daily environmental changes in the day-night cycle. In eumetazoans (bilaterians + cnidarians), this network appears to be largely conserved, yet different from other known eukaryotic circadian networks. To determine if the eumetazoan circadian network has an older origin, we ask here whether orthologues comprising this network are expressed in a manner consistent with a role in regulating circadian patterns in a representative of an earlier-branching animal lineage, the sponge Amphimedon queenslandica. The A. queenslandica genome encodes orthologues of many eumetazoan circadian genes, including two cryptochrome genes that encode flavoproteins, three Timeout genes, and two PAR-bZIP and seven bHLH-PAS transcription factor genes. There is no apparent Cycle orthologue, although we can identify three closely related ARNT genes. Of the putative circadian genes, only AqPARa and AqCry2 have a consistent oscillating diurnal expression profile, and the rhythmic expression of both these genes is partially lost when the animals are exposed to constant light or darkness. Expression of the other putative circadian genes, in particular AqClock, is neither diurnally-oscillating nor light-dependent. AqPARa and AqCry2 are also temporally and spatially co-expressed throughout embryonic and larval development. Transcripts of these genes are enriched first in cells comprising the larval posterior pigment ring, which is a simple photosensory organ that is responsible for the negative phototactic behaviour displayed by larvae, and subsequently in the larval epithelial and subepithelial layers. The combined findings of no clear Cycle orthologue and of PAR-bZIP and cryptochrome being the only orthologues expressed in a pattern consistent with a circadian role suggests that either (i) the ancestral metazoan circadian network was simpler than the eumetazoan network, or (ii) that this sponge has lost some components, as has occurred in some other animals such as Hydra.